MEDIA PEMBELAJARAN INTERACTIVE SISWA SEKOLAH DASAR (SD) MENGGUNAKAN ANIMATION MACROMEDIA FLASH 8 - Nofyta Andryani; Zulham Zulham; M. Eka (Djtechno: Jurnal Teknologi Informasi, 2023)
The current development of Information Technology forces us to always improve all scientific fields so as not to be left behind by these technological developments. This research was conducted to motivate Elementary Schools (SD) so that students are more creative in learning so that they can be interested in learning in the future. Therefore, the use of information technology is very important among students, especially elementary school (SD) students. Making interactive learning media using the Masromedia Flash 8 application in the form of animation (animation) makes Elementary School (SD) students more motivated and a greater sense of curiosity. This animation made with creativity is expected to increase the learning spirit of elementary school students. Macromedia Flash 8 has a complete menubar for creating animations, especially for learning media. The chosen method is the ADDIE method which includes: Analysis in the form of needs, students and so on. Design in the form of competency formulation, strategy. Develop in the form of teaching materials, lessons and so on. Applying in the form of face-to-face, assessment and so on. Evaluation of the improvement of learning programs